BAKABUANG PHENOMENON IN MINANGKABAU SOCIETY: A COVERT HUMAN TRAFFICKING ACTION - Nelmawarni, Nelmawarni; Kustati, Martin; Ulfatmi, Ulfatmi; Warnis, Warnis; Hallen, Hallen; Ikhwan, Ikhwan; Perrodin, David D (Universitas Islam Negeri Imam Bonjol Padang, 2021)
Bakabuang, more commonly known as cino buto, is a traditional yet destructive custom that is still practiced by the Minangkabau people by which an informally divorced couple may reconcile. This study aims to analyze the understanding of the bakabuang custom and its impact on women and children, while exploring the role and function of Tungku Tigo Sajarangan [community leaders] on the custom of bakabuang in the Minangkabau culture. This research uses a qualitative approach employing interview data, observation, and documentation. Data sources are ex-husbands and ex-wives, kadi [marriage guardians], community members, and traditional and community leaders. The results showed that bakabuang was one option offered to a married couple to reconcile after the husband had pronounced Triple Divorce/Talaq-e-Biddat/Triple Talaq [an instant irrevocable divorce that is not necessarily analogous with judgments and perceptions of Islamic scholars or jurists]. Bakabuang is usually done at the requests of children, families, and often, the couples themselves. The findings further showed that the community does not recognize that bakabuang is prohibited nor violates Islam's foundational teachings. Some claimed that bakabuang is an acceptable solution in Islam for married couples who want to reconcile but have already executed a Triple Divorce. It was also found that the impact of such practices is detrimental to women and children as most Ninik Mamak [clan leaders or elders] are aware of the bakabuang tradition. Yet, they are powerless to stop it on account of social repercussions if the practice is banned. Just as the Ninik Mamak cannot do much in responding to bakabuang, scholars are powerless; they can only convey the negative impact of bakabuang. The study recommends that the bakabuang tradition be considered a crime against humanity and classified as covert human and sex trafficking of women by the Minangkabau people of West Sumatra, Indonesia.